PENGARUH DISIPLIN, KOMPENSASI, DAN PELATIHAN TERHADAP KINERJA ANGGOTA (STUDI PADA KODIM 0719/ JEPARA) (Students' Journal of Economic and Management, 2015)
This study mangambil object on KODIM office 0719 / Jepara. The reason in the selection of objects based research because they want to know the Members performance. From these gaps it is necessary to evidence and research to analyze the influence of Discipline, compensation, and training on the performance of members. The research sample using the sample collection method is purposive sampling sampling based on characteristics that are known in advance, samples taken 100 respondents. From a population of 248 people. Methods of data analysis using linear regression and methods of data collection using the questionnaire. The test results showed that (1) Discipline affect the performance of members showed a positive and significant influence, (2) Compensation affect the performance of members showed a positive and significant influence, (3) training effect on the performance of members showed that positive and significant effect. Keywords: Discipline, compensation, training, and performance of members.